Discordance of Human Epidermal Growth Factor Receptor-2 Expression in Primary Breast Cancer and Related Axillary Lymph Node Metastasis - Naimi, Azar (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Difference in human epidermal growth factor receptor-2 (Her-2) expression in metastatic axillary lymph nodes and primary breast tumor may affect treatment response, as studies have shown that change of therapy according to lymph node metastasis biomarker expression, improved patient prognosis. The aim of current study is to evaluate the Her-2 expression in primary breast cancer (BC) and its accordance with metastatic axillary lymph nodes. Materials and Methods: This is a cross-sectional study on 70 patients with BC conducted in Isfahan University of Medical Sciences. Age, number of involved lymph nodes, Her-2, estrogen receptor (ER), and progesterone receptor expression and in case of Her-2 expression, its grade in primary BC were recorded. Her-2 expression was evaluated in the metastatic axillary lymph node by immunohistochemistry method. Results: The mean age of patients who had concordance was 51.2 Â± 13.1 and those who did not have this association was 48.9 Â± 12.1 (P = 0.45). 48.6% of samples showed discordance of primary BC and lymph node metastasis. In ER-positive patients, 42.9%, and in ER-negative group, 60%, revealed concordance. In discordance group, 50% revealed Grade 1, 43.2% Grade 2 and 61.5% Grade 3. Discussion: Lower number of metastatic lymph nodes was significantly associated with Her-2 expression concordance. Our study found positive conversion in 12.5% of patients who have primary BC negative results with positive metastatic lymph nodes and 42.1% of negative conversion. In the current study, we found a high rate of discordance of Her-2 expression in primary BC with metastatic lymph nodes. The number of metastatic lymph nodes affected Her-2 expression concordance diversely.